Mettre en place une politique de lutte contre le changement climatique en aire métropolitaine : le cas de la Région du Grand ABC au Brésil - Julie Bideux (Confins)
Local governments have recently emerged as an important level to combat climate change. It therefore becomes necessary to study what are the factors favouring policy making on the subject, and how it is implemented. Through the case of the Greater ABC Region in the Metropolitan Region of São Paulo in Brazil, we can analyse the construction of a climate policy, in a metropolitan area, by small and medium-sized cities, and through the coordination of an inter-municipal Consortium. In particular, we see how the circumstances of placing the fight against climate change on the agenda – and which actors, institutions, levels of government or sectors are involved - influence the way this policy is implemented. Thus this makes it possible to identify in part the origin of problems of institutionalization of the fight against climate change, or of the unequal distribution of the benefits of the process between municipalities and sectors.